2011
DOI: 10.1017/s1751731111000462
|View full text |Cite
|
Sign up to set email alerts
|

Dietary addition of Lactobacillus rhamnosus GG impairs the health of Escherichia coli F4-challenged piglets

Abstract: Lactobacillus rhamnosus GG (LGG) is a probiotic for humans and is normally not found in pigs; however, it has been shown to protect the human-derived intestinal Caco-2 cells against the damage induced by an important intestinal pathogen, enterotoxigenic Escherichia coli F4 (ETEC). An experiment was conducted to test whether the dietary addition of LGG improves the growth and health of weaned pigs when orally challenged by E. coli F4. Thirty-six pigs were weaned at 21 days and assigned to a standard weaning die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…For example, a host Lactobacillus strain reduces STEC shedding in beef cattle, but does not affect performance [41], while a host Lactobacillus strain reduced pig performance after an E. coli F4 challenge which resulted in greater E. coli F4 shedding [42]. Adding to this confusion, non-host probiotics and prebiotics increase milk production [43], alleviate disease [3,4] and decrease pathogen shedding [44], but the responses are quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a host Lactobacillus strain reduces STEC shedding in beef cattle, but does not affect performance [41], while a host Lactobacillus strain reduced pig performance after an E. coli F4 challenge which resulted in greater E. coli F4 shedding [42]. Adding to this confusion, non-host probiotics and prebiotics increase milk production [43], alleviate disease [3,4] and decrease pathogen shedding [44], but the responses are quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…can alleviate disease signs of S . Typhimurium infection in weaned pigs (Casey et al, 2007), but several clinical trials have reported risks associated with LGG administration (Trevisi et al, 2011; Doron and Snydman, 2015). However, the exact mechanism underlying the activity of LGG against pathogenic microorganisms and its regulation of immune responses during Salmonella infection is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Restoration of a balanced gut microbiota through the application of probiotic microbes could help to prevent the development of GI infections around weaning. Beneficial effects of bacterial supplementation have been reported in enterotoxigenic Escherichia coli (ETEC) and Salmonella challenge studies in pigs (Casey et al, 2007;Konstantinov et al, 2008;Lee et al, 2012), albeit not all studies have reported favorable outcomes (Trevisi et al, 2011;Kreuzer et al, 2012;Walsh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%